Prevalence of periodontopathogens and Candida spp. in smokers after nonsurgical periodontal therapy - a pilot study - Camargo, Gabriela Alessandra da Cruz Galhardo; Abreu, Mariana Gouvêa Latini; Cordeiro, Renata Dos Santos; Wenderoscky, Letícia de Farias; Duque, Cristiane (FapUNIFESP (SciELO), 2016)
This pilot study aimed to evaluate the influence of smoking on clinical and microbiological parameters after nonsurgical periodontal therapy. Forty-eight subjects were grouped into smokers (SM, n = 24) and nonsmokers (NS, n = 24) and paired according to gender, age, ethnicity, and periodontal status. Both groups received oral hygiene education and scaling and root planing. Clinical evaluation was performed using plaque index (PI), bleeding on probing (BOP), pocket probing depth (PPD), gingival recession (GR), and clinical attachment level (CAL) before instrumentation (baseline) and at 3 and 6 months. The prevalence of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Tannerella forsythia, Candida albicans, Candida glabrata, Candida tropicalis, and Candida dubliniensis in subgingival biofilm was determined by polymerase chain reaction. The data were statistically analyzed considering p < 0.05. Clinical conditions improved between baseline and 3 months after periodontal treatment. However, NS had a better clinical response, presenting greater PPD reduction and CAL increase in comparison to SM. Periodontal treatment reduced the levels of P. gingivalis, A. actinomycetemcomitans, and T. forsythia individually after 3 months for the NS group and after 6 months for both groups. The prevalence of Candida species was markedly higher in SM than in NS at all time points evaluated. Periodontopathogens associated or not with C. albicans or C. dubliniensis were more prevalent in SM than in NS at baseline and after 3 months. It was concluded that smoking impairs clinical and microbiological responses to periodontal therapy. Periodontopathogens combined or not with some Candida species are resistant to short-term periodontal therapy in SM.